2012
DOI: 10.1108/17538391211233399
|View full text |Cite
|
Sign up to set email alerts
|

The conflicts of interest inside theShari'asupervisory board

Abstract: Purpose -The purpose of this study is to identify the relation between the conflicts of interest in the Shari'a Supervisory Board (SSB) in the Islamic financial institutions (IFIs) and six independent variables: the SSB executive position, the SSB remuneration, the relation between the SSB members and the Board of Directors (BoD), and the multiple memberships in Islamic funds, issuers of Islamic bonds (Sukuk), and companies trading in capital markets. Design/methodology/approach -The variables are articulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 13 publications
(7 reference statements)
0
18
0
Order By: Relevance
“…He found that there are significant differences across the countries, which indicated that there are weaknesses to the existing international Sharia’ah governance requires more attention and improvement. Nathan Garas (2012) studied the conflicts of interest between the Sharia’ah board and board of directors. He concludes that the conflict of interest in the Sharia’ah board is significantly affected by the executive members.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…He found that there are significant differences across the countries, which indicated that there are weaknesses to the existing international Sharia’ah governance requires more attention and improvement. Nathan Garas (2012) studied the conflicts of interest between the Sharia’ah board and board of directors. He concludes that the conflict of interest in the Sharia’ah board is significantly affected by the executive members.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…On the other hand, some other studies examine the impact of standards issued by Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) on disclosure of Islamic financial institutions in different countries. These standards promote transparency, disclosure and comparability of financial reporting of Islamic financial institutions across countries (Garas, 2012). Grais and Pellegrini (2006) argue that the implementation of AAOIFI standards increases the level of voluntary disclosures.…”
Section: Shari'ah Governance Disclosurementioning
confidence: 99%
“…Several studies have discussed the CG from an Islamic perspective, current SG practices and issues, challenges of good SG, different SG models and systems across jurisdictions (see, e.g., Grais and Pellegrini, 2006a; Grais and Pellegrini, 2006b; Hasan, 2009; Nathan Garas and Pierce, 2010; Nathan, 2010; Hasan, 2011; Abdullah Saif Alnasser and Muhammed, 2012; Nathan Garas, 2012a, 2012b; Grassa, 2013; Hamza, 2013; Grassa and Matoussi, 2014b; Ayedh and Echchabi, 2015; Sulaiman et al , 2015; Grassa, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, some of these studies are descriptive (see, e.g., Hasan, 2011; Grassa and Matoussi, 2014b), while some other studies are empirical (see, e.g., Nathan, 2010; Nathan Garas, 2012a). Despite the last two studies being empirical, they only focused on the SSB performance and function, and they did not link the SSB to the bank performance.…”
Section: Resultsmentioning
confidence: 99%